The importance of community-family relations in the development of civil society - Kholov Ilhom (Academia One Publishing, 2023)
This article provides information about importance of neighborhood-family relations in the development of civil society in Uzbekistan is highlighted on the example of our historical traditions and values
Keywords: civil society; neighborhood; family